Utilization of Home Yards for Making Vertical Planting Media in the Dasan Geres Tengah Environment, Dasan Geres Village, Gerung District, West Lombok Regency - Handriani, Handriani; Syamsuddin, Syamsuddin; Kormil Saputra; Rahmatun Inayah; Ika Umratul Asni Aminy; Adella Ulyandana Jayatri (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
The Dasan Geres Tengah neighborhood of Dasan Geres Village, Gerung District, West Lombok Regency, has a standard economic condition because the community has an average livelihood as Farmers and Traders. The role in contributing to creating new skills to be developed in the village by young men and women and housewives in particular is not very exposed by the people in the area. In this regard, the role of youth groups and housewives in the Dasan Geres Tengah neighborhood is expected to be able to create initiatives in making simple skills activities, a small example of which is the use of land in developing food houses that can be used continuously, so that it can be useful in helping to facilitate the basic daily needs of housewives in particular.